DIETARY EXPOSURE TO ESSENTIAL AND TOXIC ELEMENTS FROM FRESH, PASTEURISED AND POWDER MILK SAMPLES FROM PAKISTAN - Fatima, I.; Wasim, W.; Rehman, S. (The Nucleus, 2011)
This study assesses the intake adequacy of elements determined in fresh, ultra high temperature treated and powder milk samples. The samples were analysed by semi-absolute k0 instrumental neutron activation analysis, epithermal neutron activation analysis and flame atomic absorption spectrophotometry with proper method validation. Fourteen elements (Br, Ca, Cl, Cs, Cu, Fe, K, Mg, Na, P, Rb, Sn, Sr and Zn) were quantified in all samples. All essential elements were assessed for their daily intake by comparing with the dietary reference intakes. The daily intake of Pb, identified in only two samples, was compared with the provisional tolerable weekly intake defined by FAO/WHO. The Sr/Ca ratio was calculated for the assessment of radioactive dose. Additionally, the data was explored by cluster analysis and correlation coefficient to extract relationships between samples and elements respectively